Design of LDPC Decoder Based On FPGA in Digital Image Watermarking Technology - Zhongxun Wang; Tiantian Tang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
LDPC code and digital image watermarking technology, which is an effective method of digital copyright protection and information security, has been widely used. But this is a multi-disciplinary, multi technology application scheme. In order to realize FPGA design of LDPC decoder in the application scheme, an effective implementation method of digital watermarking application system must be found. In this paper, MATLAB software and Qt development environment are combined to achieve the digital watermarking application software design. It could get real-time input data for the LDPC decoder. Then the hardware of the LDPC decoder is primarily implemented by FPGA in the digital image watermarking system. And the serial port is used to make the output data of the decoder back to computer for verification. Through the simulation results, the Modelsim time simulation diagram is given, and the watermark image compared with the original image is got. The results show that the resource usage of our system is few, and the decoding rate is fast. It has a certain practical value.